The effect of lamina configuration on low-velocity impact behaviour for glass fiber/rubber curved composites - Albayrak, Mustafa; Kaman, Mete Onur; Bozkurt, Ilyas (Sage Publications Ltd, 2023)
The aim of this study is to produce curved sandwich composites with different arrays by adding Ethylene Propylene Diene Monomer (EPDM) rubber interlayers between glass fiber woven fabrics and to investigate their behaviours under low-velocity impact. For this purpose, sandwich plates were produced through the vacuum infusion method by using glass fiber and rubber layers on the steel mold manufactured in curved form. Impact tests were applied on the plates and the effect of the stacking sequence for glass fibers/rubber layer on the impact energy absorption was examined. The energy absorption property of the composites was improved by a maximum of 45% with a layer epdm used in the midplane of the composite. Also, when rubber layers were used on the outermost surface of the composites, the damage area reduced by 14%. In the numerical part, the tests were modelled using LS-DYNA finite element packaged programme and the Hashin failure criterion-based material model was used in order to view any damages on the composite structure after the tests. The agreement between numerical and experimental results was obtained with a maximum error of 19%
Keywords: Curved composites; rubber layer; progressive failure analysis; low-velocity impact